Expert opinion on using angler Smartphone apps to inform marine fisheries management: status, prospects, and needs. (19th January 2021) - Skov, Christian; Hyder, Kieran; Gundelund, Casper; Ahvonen, Anssi; Baudrier, Jérôme; Borch, Trude; deCarvalho, Sara; Erzini, Karim; Ferter, Keno; Grati, Fabio; van derHammen, Tessa; Hinriksson, Jan; et al.
Abstract: Smartphone applications (apps) that target recreational fishers are growing in abundance. These apps have the potential to provide data useful for management of recreational fisheries. We surveyed expert opinion in 20, mostly European, countries to assess the current and future status of app use in marine recreational fisheries. The survey revealed that a few countries already use app data to support existing data collection, and that this number is likely to increase within 5–10 years. The strongest barriers to use app data were a scarcity of useful apps and concern over data quality, especially biases due to the opt-in nature of app use. Experts generally agreed that apps were unlikely to be a "stand-alone" method, at least in the short term, but could be of immediate use as a novel approach to collect supporting data such as, fisheries-specific temporal and spatial distributions of fishing effort, and aspects of fisher behaviour. This survey highlighted the growing interest in app data among researchers and managers, but also the need for government agencies and other managers/researchers to coordinate their efforts with the support of survey statisticians to develop and assess apps in ways that will ensure standardisation, data quality, and utility.